Hybrid-AI-sep: A multi-agent computer-aided tool for separation process problems solving and learning - Prasopsanti, Kris; Yadbantung, Rungroj; Phanusupawimol, Thunyaras; Areerat, Surat; Mansouri, Seyed Soheil; Savoie, Christopher J.; Gani, Rafiqul (My University, 2026)
AbstractThis paper presents a multi-agent based and artificial intelligence augmented computer-aided software tool, Hybrid-AI-sep, with problem solving and education modules for the important topic of design of separation operations. Three types of agents are employed by Hybrid-AI-sep, a library of knowledge-tools containing theory, concepts, and glossary terms related to separation operations; a library of database tools consisting of different types of measured data; and a library of computational tools that generate problem specific data that may be needed for decision making and explanation for the problem solution and educational modules. The paper presents software architecture together with examples of the three types of agents. Illustrative examples highlighting various features of Hybrid-AI-sep are given in the main manuscript and the supplementary material.
Keywords: Artificial intelligence; Multi-agent system; Problem solving, Learning, Software; Process systems engineering; Separation processes